2018
DOI: 10.3177/jnsv.64.483
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Sensitization to Soybean Proteins Is Attenuated by Oral Tolerance

Abstract: Oral tolerance prevents allergic responses, but cutaneous exposure to food allergens predisposes individuals to food allergies. Soybean, a major allergenic food, is also an ingredient in various cosmetic products. However, it remains to be determined whether oral tolerance prevents percutaneous sensitization to soybean proteins in humans or animal models. In this study, BALB/c mice were divided into three groups; the SS group fed a soybean-containing diet, and the CS and control (C) groups fed a soybean-free d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…Previously, we identified that principal soybean allergens Gly m 5 and Gly m 6 trigger percutaneous sensitization in a mouse model (9). Using the same model, the soybean trypsin inhibitor Gly m TI was also identified as a soybean allergen that causes percutaneous sensitization (10). These food allergens are also the primary soybean allergens in humans, suggesting that a mouse model can be effectively used for the identification of allergens that cause percutaneous sensitization in humans.…”
Section: Popular Scientific Summarymentioning
confidence: 91%
“…Previously, we identified that principal soybean allergens Gly m 5 and Gly m 6 trigger percutaneous sensitization in a mouse model (9). Using the same model, the soybean trypsin inhibitor Gly m TI was also identified as a soybean allergen that causes percutaneous sensitization (10). These food allergens are also the primary soybean allergens in humans, suggesting that a mouse model can be effectively used for the identification of allergens that cause percutaneous sensitization in humans.…”
Section: Popular Scientific Summarymentioning
confidence: 91%
“…(2004) показали, что иммунный ответ, вызванный транскутанным воздействием аллергена, направлен в сторону Th2-пути. Такая реакция была получена при воздействии различных антигенов и у различных видов мышей [12][13][14][15][16]. Микроповреждения кожи в этих исследованиях являются моделью дефекта кожного барьера, который отмечается у больных с атопическим дерматитом.…”
Section: экспериментальные модели формирования пищевой сенсибилизацииunclassified
“…Например, в Норвегии при исследовании образцов пыли в 143 домах аллерген рыбы был обнаружен в 46%, арахиса -41%, молока -39% и аллерген яйца -22% образцов пыли матраса [58]. Пищевые аллергены могут содержаться в косметических средствах, используемых для базовой терапии атопического дерматита, что приводит к непосредственному контакту пищевых белков с пораженной кожей [16,59]. Анализ данных исследования с участием 13 971 ребенка дошкольного возраста показал значимую связь аллергии на арахис с применением средств ухода за кожей, содержащих арахисовое масло [60].…”
Section: роль золотистого стафилококка в формировании транскутанной с...unclassified
“…It has been reported that allergic reactions by percutaneous sensitization are caused by various foods. In our previous studies, we identified the major percutaneously sensitizing allergen candidates in soybean [ 3 , 4 ], cherry [ 5 ], and kiwi [ 6 ]. Ovalbumin (OVA) and lactoglobulin were also reported to be percutaneously sensitizing allergens in egg and milk, respectively [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%